Assessing health-related quality of life in women who use contraceptives - ديبو, مرح (Latakia University Journal -Medical Sciences Series, 2024)
The quality of life of women of reproductive age has become an important aspect of the social and economic well-being of countries with high population growth. Family planning and women's quality of life are topics of great importance to practitioners and researchers. The use of contraceptives may affect the psychological, social, sexual, physiological aspects and health status of women. Objective: This research aims to evaluate the health-related quality of life of women who use contraceptives. Research tools and methods: This research was conducted on a sample of 200 women who use contraceptives at the Al-Hussein Health Center in the city of Tartous Results: This study found that the quality of life assessment in all study axes for those who use non-hormonal contraceptives is higher than for those who use hormonal contraceptives. The best contraceptive method that had a positive impact on quality of life was the safe period and amputated intercourse with an average of (3.83) for each, then condoms with an average of (3.75), the IUD with an average of (3.65), and birth control pills - intramuscular injections with an average of (2.76)